78‐3: Distinguished Paper: Flexible AMOLED Displays with Bending Interactive Interface. Issue 1 (May 2016) - Tu, Chia-Hsun; Chang, Chia-Chun; Chen, Ji-Feng; Hsu, Ming-Chang; Hsieh, Wei-Jung; Wang, Wen-Ting; Chang, Cheng-Hao; Lai, Yen-Huei; Wang, Wan-Tsang; Hsu, Che-Ming; Lin, Hong-Shen; Hwu, Keh-long; et al.
Abstract : The human‐machine interaction provides effective operation and control of the machine on the users' end, and feedback from the machine. Flexible display prevails over the conventional flat display by its ability to change the display geometric appearance, and can provide alternative user‐display interactions. In this paper, a bendable phone technology with flexible AMOLED display and a novel bending interactive interface has been disclosed. The bending interface provides a more intuitive operation for users